Anti-hypercholesterolemia, Anti-atherogenic, and Anti-hypertension Effects of Red Beetroot (Beta vulgaris L.) in Rats Induced by High Fat and Fructose Diet - Alim El-Hakim; Sunarti Sunarti; Lisna Hidayati; Slamet Widiyanto (Journal of Tropical Biodiversity and Biotechnology, 2023)
Metabolic syndrome is associated with abnormalities of lipid levels in the blood such as hyperlipidemia. Hyperlipidemia conditions can increase the risk of atherosclerosis and hypertension. Beetroot (Beta vulgaris L.) is a plant that contains high antioxidants. Beetroot has the potency to be used as a functional food that can reduce the potential for atherosclerosis and blood pressure. The aim of this study was to examine the effect of beetroot-enriched feed on the cholesterol level, atherogenic index and blood pressure of rats (Rattus norvegicus Berkenhout, 1769) induced by high fat and fructose diet. As many as 25 rats were divided into control, hyperlipidemia, and three treatment groups. The hyperlipidemia and treatment groups were induced to become hyperlipidemia using AIN93-M modified high fat and fructose feed for 8 weeks. The treatment groups were followed by intervention with 6, 9, and 12% beetroot enriched feed for 6 weeks. The feed was prepared by mixing beetroot flour in the pellets. Blood pressure, total cholesterol, and HDL level measurement was conducted after hyperlipidemia induction and after the intervention. The data analyzed with one-way ANOVA, DMRT, and T-Test. The results showed that 6% beetroot intervention have the highest increasing of HDL-cholesterol than other groups. The 9% beetroot intervention significantly decrease total cholesterol lower than normal baseline, and 12% beetroot intervention significantly decrease blood pressure than other groups. The atherogenic index of all treatment group was decreased. The 9% beetroot enriched feed was seen as an optimum dose to reduce total cholesterol, atherogenic index and blood pressure and increase HDL-cholesterol.